The Prognostic Value of Platelet-to-Lymphocyte Ratio and Tricuspid Regurgitation Velocity in Patients with Light-Chain Myocardial Amyloidosis - Zhu Y; Gong C; Hu J; Gao T; Feng C; Yang C; Wang Y (Journal of Inflammation Research, 2025)
Yingxin Zhu, Chen Gong, Jinglin Hu, Tiankuo Gao, Cuicui Feng, Chun Yang, Yini Wang Department of Hematology, Beijing Anzhen Hospital, Capital Medical University, Beijing, People’s Republic of ChinaCorrespondence: Chun Yang, Department of Hematology, Beijing Anzhen Hospital, Capital Medical University, 2 Anzhen Road, Chaoyang District, Beijing, 100029, People’s Republic of China, Email dlmuyc29@163.com Yini Wang, Department of Hematology, Beijing Anzhen Hospital, Capital Medical University, 2 Anzhen Road, Chaoyang District, Beijing, 100029, People’s Republic of China, Email wangyini@ccmu.edu.cnPurpose: To explore the prognostic value of inflammatory indexes and novel echocardiographic parameters in light-chain myocardial amyloidosis (AL-CA) patients.Methods: We retrospectively collected clinical, laboratory, electrocardiography and echocardiographic parameters of patients. The prognostic value of inflammation indexes and echocardiographic parameters was assessed, and the association of inflammation indexes with cardiac function and the type of light chain (AL) was analyzed.Results: In total, 83 biopsy-proven AL-CA patients were studied (age: 61.42± 10.7 years; 68.7% male). The inflammation indexes [PLR (Platelet-to-Lymphocyte ratio), NLR (Neutrophil-to-Lymphocyte ratio), NMLR ((Neutrophil+Monocyte)-to-Lymphocyte ratio), SIRI ((Monocyte × Neutrophil)-to-Lymphocyte ratio), SII ((Platelet × Neutrophil)-to-Lymphocyte ratio), (all P< 0.001)] and echocardiographic parameter TRV (Tricuspid Regurgitation Velocity), (P=0.005) were significantly higher in deceased patients compared with survivors. Multivariate COX regression analysis indicated that PLR, TRV, Lymphocyte (LYM) and Left Ventricular Ejection Fraction (LVEF) were independent outcome predictors. The PLR, TRV, and the combined indicator (PLR+TRV) showed great value in predicting short-term prognosis. The likelihood ratio χ 2 test showed that PLR and TRV added predictive values to the Mayo04, Mayo12, and Euro15 models. The Spearman correlation analysis demonstrated a positive correlation between the inflammation indexes and New York Heart Association (NYHA) class, Mayo04 stage, Mayo12 stage, and Euro15 stage. Additionally, the NLR (P< 0.001), NMLR (P=0.002), SIRI (P=0.029), and SII (P< 0.001) were higher in Lambda than in Kappa light-chain patients.Conclusion: Our study revealed that PLR and TRV were valid predictors of short-term survival in AL-CA, and the levels of several inflammation indexes correlated with the severity of cardiac involvement and AL subtype.Keywords: light-chain myocardial amyloidosis, inflammatory index, tricuspid regurgitation velocity, prognosis